2015
DOI: 10.1039/c5sm00168d
|View full text |Cite
|
Sign up to set email alerts
|

Dual-responsive shape memory hydrogels with novel thermoplasticity based on a hydrophobically modified polyampholyte

Abstract: Shape memory hydrogels offer the ability to recover their permanent shape from temporarily trapped shapes without application of external forces. Here, we report a novel dual-responsive shape memory hydrogel with characteristic thermoplasticity. The water-insoluble hydrogel is prepared by simple ternary copolymerization of acrylamide (AM) and acrylic acid (AA) with low amounts of a cationic surfmer, in the absence of organic crosslinkers. Through either ionic/complex binding of carboxyl groups via trivalent ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 50 publications
0
35
0
Order By: Relevance
“…A hydrophobic polyampholyte SMH reported by Yang et al possesses a unique thermoplasticity, which can change its permanent shape upon heating. 52 Through either ligand-ion bindings or salt-dependent hydrophobic association, temporary shapes can be memorized. Recently, a novel dual crosslinked single-network hydrogel has been fabricated through copolymerization of acrylamide (AAm) and AAc with n-octadecyl acrylate.…”
Section: Smhs With Thermoplasticitymentioning
confidence: 99%
“…A hydrophobic polyampholyte SMH reported by Yang et al possesses a unique thermoplasticity, which can change its permanent shape upon heating. 52 Through either ligand-ion bindings or salt-dependent hydrophobic association, temporary shapes can be memorized. Recently, a novel dual crosslinked single-network hydrogel has been fabricated through copolymerization of acrylamide (AAm) and AAc with n-octadecyl acrylate.…”
Section: Smhs With Thermoplasticitymentioning
confidence: 99%
“…This enhancement demonstrated that physical crosslinkers were formed to provide sufficient strength for the gel locking a temporary shape. [38] After exposure to simulated sunlight irradiation in the presence of reductive citric acid for 2 h (the photoreduction of Fe(III) to Fe(II) ions was demonstrated in Figure S5, Supporting Information), the storage modulus G′ and loss modulus G″ recovered to the original values, indicative of the disassociation of acrylic acid-Fe(III) complexes. [37]…”
Section: Effect Of Temperature/fe(iii) On the Properties Of Hydrogelsmentioning
confidence: 97%
“…The ability to instill shape memory characteristics using ionic interactions is not limited to hydrophobic polymers as evidenced by recent reports of ion containing shape memory hydrogels (SMH). [114][115][116][117] For example, a dual-responsive SMH based on acrylamide (AM), acrylic acid (AA), and a low concentration (1.5 mol %) of cationic surfmer (Dimethylhexadecyl[2(dimethylamino)ethylmethacrylate]ammonium bromide) (C16DMAEMA) was recently reported. 116 Physical crosslinks used for temporary shape programming could be accomplished either through ion/complex associations between Fe 31 and carboxyl groups or salt-strengthened hydrophobic interactions.…”
Section: Ionic Interactionsmentioning
confidence: 99%
“…[114][115][116][117] For example, a dual-responsive SMH based on acrylamide (AM), acrylic acid (AA), and a low concentration (1.5 mol %) of cationic surfmer (Dimethylhexadecyl[2(dimethylamino)ethylmethacrylate]ammonium bromide) (C16DMAEMA) was recently reported. 116 Physical crosslinks used for temporary shape programming could be accomplished either through ion/complex associations between Fe 31 and carboxyl groups or salt-strengthened hydrophobic interactions. Shape recovery is triggered for ion complexes by introducing a reducing agent (ascorbic acid), whereas shape recovery of the hydrophobic domain is induced by deionized water.…”
Section: Ionic Interactionsmentioning
confidence: 99%